Market fairness and efficiency: Evidence from the Tokyo Stock Exchange - Kemme, David M.; McInish, Thomas H.; Zhang, Jiang (Journal of Banking & Finance, 2022)
In 2015 the Tokyo Stock Exchange (TSE) implemented Arrowhead Renewal improvements (ARI) that reduced latency from about one millisecond to less than 0.5 ms. Simultaneously, the ARI introduced new risk management functions to improve market fairness by reducing manipulative trading strategies. We find a dramatic improvement in market fairness as proxied by marking-the-close incidents, which declined by 61.19%. We find a much smaller improvement in market efficiency. Specifically, there was a reduction in the effective (quoted) spread of 6.45% (5.79%). The most dramatic improvement in market quality (fairness and efficiency) was for low-tick-size and high-market-capitalization stocks.